2006
DOI: 10.1143/jjap.45.3526
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, Optical and Material Properties of ZnO-Doped Indium–Tin Oxide Films Prepared Using Radio Frequency Magnetron Cosputtering System at Room Temperature

Abstract: The relationship between the electrical, optical and material properties of transparent and conductive oxide films prepared by rf cosputtering indium–tin oxide (ITO) and zinc oxide (ZnO) targets has been investigated. The evolution from polycrystalline structure of an undoped ITO film to an amorphous-like ZnkIn2O3+k structure obtained from ZnO-doped ITO films is found to be responsible for the marked improvement in the electrical properties. A low surface roughness is also achieved from this amorphous structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These results were indicated that the existence of excess ZnO impurities not only decreased the film resistivity, but also promoted the decrement of electron mobility [15,16]. In addition, regardless of the Zn contents, the average transmittance in visible region (390-800 nm) of pure ITO film and all ZITO films possessed an excellent transparency (over 87%).…”
Section: The Effects Of Zn Atomic Concentrationmentioning
confidence: 84%
“…These results were indicated that the existence of excess ZnO impurities not only decreased the film resistivity, but also promoted the decrement of electron mobility [15,16]. In addition, regardless of the Zn contents, the average transmittance in visible region (390-800 nm) of pure ITO film and all ZITO films possessed an excellent transparency (over 87%).…”
Section: The Effects Of Zn Atomic Concentrationmentioning
confidence: 84%
“…Binary compounds like doped indium oxide, zinc oxide, and tin oxide are widely used because they present unique electrical and optical properties. Zinc indium tin oxide (ZITO) alloys have been previously studied and improvements in electrical 3,4 and mechanical 5 properties compared to indium tin oxide (ITO) were reported for certain compositions. The objective of the presented experiments was to characterize the electronic structure (i.e., work function and band edge energies) of ZITO thin films in order to assess their suitability for electrode applications.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed deposition conditions of the cosputtered AZO (defined as cosputtered Al-ZnO, hereafter) films are given in Table I. Similar to the reports on the preparation of cosputtered ITO-ZnO and AlN-ZnO films, 31,32) the theoretical Al atomic ratios [Al=ðAl þ ZnÞ at. %] cosputtered into the ZnO films were evaluated to be 5, 7.5, 9, 10, 12.5, and 15 at.…”
Section: Methodsmentioning
confidence: 99%